2017
DOI: 10.1038/s41430-017-0037-2
|View full text |Cite
|
Sign up to set email alerts
|

Associations of genetic determinants of serum vitamin B12 and folate concentrations with hay fever and asthma: a Mendelian randomization meta-analysis

Abstract: Link to publication record in Explore Bristol Research PDF-document This is the author accepted manuscript (AAM). The final published version (version of record) is available online via Nature at http://www.nature.com/articles/s41430-017-0037-2. Please refer to any applicable terms of use of the publisher. University of Bristol -Explore Bristol Research General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
0
11
1
Order By: Relevance
“…Our study also found a positive association between dietary vitamin B12 and childhood asthma, which is inconsistent with the findings of current epidemiological studies (25,26). However, it is theorized that vitamin B12 may influence asthma risk by affecting DNA methylation.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study also found a positive association between dietary vitamin B12 and childhood asthma, which is inconsistent with the findings of current epidemiological studies (25,26). However, it is theorized that vitamin B12 may influence asthma risk by affecting DNA methylation.…”
Section: Discussioncontrasting
confidence: 99%
“…Most asthma definitions were based on self‐reported physician diagnosed asthma, some included wheezing and/or asthma treatment, others relied on hospital contact. Classification of atopic and non‐atopic asthma was based on different methods including fractional exhaled nitric oxide measurements, 17 having allergic rhinitis in combination with use of allergy medication or reported allergic symptoms, 18 positive skin prick test, 13 or investigated allergic sensitization defined as specific IgE positivity to one or more inhalant allergens 19 (Supplementary Results S1).…”
Section: Resultsmentioning
confidence: 99%
“…Skaaby et al. (quality score 10) investigated the association of serum levels of B12 and folate with asthma and hay fever risk, but found no evidence for causation 19 . Neither did Granell et al.…”
Section: Causal Risk Factors For Asthma and Respiratory Allergymentioning
confidence: 99%
“…Serum folate levels are associated with serum IgE, high plasma folate is associated with decreased risk of wheezing, and folic acid supplementation has been linked with an increased risk for lung cancer . Folate can be produced by most Bacteroidetes, Fusobacteria, and Proteobacteria, but rarely from Actinobacteria and Firmicutes .…”
Section: Metabolites Critically Shape the Microbiomementioning
confidence: 99%